2023
DOI: 10.1177/17571774231165410
|View full text |Cite
|
Sign up to set email alerts
|

Late poor outcomes of Clostridioides difficile infections in oncological patients: A multicentre cohort study

Abstract: Background Cancer has been associated with an increased risk of in-hospital mortality in CDI patients. However, data on delayed mortality in cancer patients with CDI are scarce. Aim/Objective The aim of the present study was to compare outcomes between oncological patients and the general population with Clostridioides difficile infection (CDI) after 90 days of follow-up. Methods A multicenter prospective cohort study was conducted in 28 hospitals participating in the VINCat program. Cases were all consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Our apparent less frequent recurrence compared to individuals without cancer may seem contra-intuitive and contrary to some previous studies which have suggested increased recurrence [ 50 52 ]. Yet, previous meta-analyzes did not find strong evidence for an association [ 14 16 ], and other studies show similar results [ 12 , 53 ]. The inclusion of community-acquired CDI in our study probably made little difference, as 97% of those with ongoing cancer was deemed health-care acquired compared to 90% of those without cancer.…”
Section: Discussionmentioning
confidence: 81%
“…Our apparent less frequent recurrence compared to individuals without cancer may seem contra-intuitive and contrary to some previous studies which have suggested increased recurrence [ 50 52 ]. Yet, previous meta-analyzes did not find strong evidence for an association [ 14 16 ], and other studies show similar results [ 12 , 53 ]. The inclusion of community-acquired CDI in our study probably made little difference, as 97% of those with ongoing cancer was deemed health-care acquired compared to 90% of those without cancer.…”
Section: Discussionmentioning
confidence: 81%
“…51 Calbo investigated CDI in patients with cancer, and found a higher risk of CDI recurrence (13%) and mortality (27%), particularly late mortality (3 months after initial episode: 13%). 52 Calbo concluded that in select populations (the elderly, patients with cancer, and patients with recurrent CDI), delayed mortality rates may be higher than early mortality rates. For the initial CDI, 63.5% of the audience selected fidaxomicin (200 mg twice daily [BID] for 10 days) as the best therapy for this patient, while 30.4% selected vancomycin (125 mg QID for 10 days), and 6.1% chose metronidazole (500 mg three times daily for 10 days).…”
Section: Understanding the Risk Factors And Outcomes Of Recurrent Clo...mentioning
confidence: 99%